Pancreatic Ductal Adenocarcinoma in a Wistar Hannover GALAS Rat - Kuroda, Yusuke (Japanese Society of Toxicologic Pathology, 2013)
There are no reported spontaneous cases of pancreatic ductal adenocarcinoma (PDAC), and there are few reports about chemically-induced PDAC in rats. We encountered a PDAC in a Wistar Hannover GALAS rat that had been subjected to a medium-term multiorgan carcinogenicity bioassay. This article describes the histological and histochemical findings of the tumor. The tumor was located in the pancreatic tissue and had not invaded the liver parenchyma or the mucosal layer of the alimentary tract. The tumor cells were atypical and were mainly arranged in small tubules. In addition, abundant stroma and mucus production were observed in the tumor. In an immunohistochemical examination, the tumor cells were positive for cytokeratin, Sox9 and pancreas duodenum homeobox 1 and negative for amylase 2A and insulin. Therefore, the tumor was diagnosed as a PDAC based on its histological and histochemical findings. We considered that the tumor was caused by the carcinogens administered during the abovementioned bioassay.